Issues and opportunities in primary health care for children in Europe : the final summarised results of the Models of Child Health Appraised (MOCHA) project - Blair, Mitch; Rigby, Michael; Alexander, Denise, 1970- (Bingley, U.K. : Emerald Publishing Limited, 2019)
The ebook edition of this title is Open Access and freely available to read online. This book reports on a project which studied of how primary care services are delivered to children. The study, the first of its kind, has been undertaken over three years, with 20 scientific partners, and an expert agent in each country. Chapters address key questions such as professional patterns, service structure, and e-health. But it also addresses cross-cutting issues which have emerged, such as equity, listening to children and parents, quality, children's increasing autonomy across the life course, and inter-professional coordination. Summarising the current policies for children's primary care in each country in the EU/EEA, authors consider the differences of structure and delivery, and of outcomes including financing, professional education, e-health and other supports.
Prelims -- The MOCHA project: origins, approach and methods -- Models of primary care and appraisal frameworks -- Listening to young people -- Child centricity and children's rights -- Equity -- The limited inclusion of children in health and health-related policy -- The invisibility of children in data systems -- The conundrum of measuring children's primary health care -- Measurement conundrums: explaining child health population outcomes in MOCHA countries -- Services and boundary negotiations for children with complex care needs in Europe -- School health services -- Primary care for adolescents -- Workforce and professional education -- E-health as the enabler of primary care for children -- Affiliate contributors to primary care for children -- The transferability of primary child healthcare systems -- National and public cultures as determinants of health policy and production -- Bringing MOCHA lessons to your service -- Evidence to achieve an optimal model for children's health in Europe -- Appendix 1: List of MOCHA scientists -- Appendix 2: List of MOCHA country agents -- Index.
Includes index.
Keywords: Child health services -- European Union countries; Primary care (Medicine) -- European Union countries; Health & Fitness -- Health Care Issues; Health systems & services